Design a novel rectangular MPCVD reactor operated at 2.45 GHz for diamond growth: A simulation-based study - Caijie Zhang; Kai Wang; Shixian Cai; Tingru Zhu; Jie Li; Zhiying Xu; Jinghui Wang; Kedong Wang; Guohui Wei; Xueqing Yan; Kun Zhu (AIP Advances, 2025)
The electric field distribution within a microwave plasma chemical vapor deposition (MPCVD) reactor determines the quality of synthetic diamonds. In this study, we aimed to facilitate diamond deposition for various demands by designing a rectangular MPCVD reactor that can balance and regulate the electric field intensity and uniformity in the deposition region. Establishing and utilizing a 3D numerical model, we analyzed the electromagnetic field and plasma distributions of three reactor candidates. One promising candidate was optimized and compared with two cylindrical cavities, each having a diameter equal to the width and diagonal length of the rectangular cavity, respectively. The optimized rectangular reactor combined the TM011, TM021, and TM031 modes, exhibited a high-intensity and uniform electric field in the deposition region without other hot-spot regions, and demonstrated high-density plasma and uniform gas distribution. Operating at 2.45 GHz, the reactor generated a maximum electric field intensity of 2 × 105 V/m, and the hydrogen plasma reached a maximum electron density of 5.9 × 1017 m−3 over an effective area of 4.0 × 103 mm2 at 5 kW power and 20 kPa pressure. These findings highlight the potential of the rectangular reactor design, which exhibits a novel microwave modes coupling mechanism, enabling redistribution of microwave energy, and achieves higher electric field intensity in the deposition region compared with traditional cylindrical reactors. The study emphasizes the significance of the rectangular reactor for the growth of demand-specific diamonds.